Bats ectoparasites infracommunities structure patterns and interactions - Guilherme Douglas Piel Dornelles (2021)
Parasite community structures result from a complex chain of interactions. These organisms interact with their hosts, conspecifics, and other parasites species, in addition to environmental requirements. Some of these structuring processes can be accessed using Metacommunity Theory. This theory mainly focuses into evaluate patterns and mechanisms contributing to species diversity across space, usually in local and reginal scales. The local scale approach can be used to explore infracommunity structural processes. Infracommunity is the term used to identify all parasites of a particular individual host, and it shares some of characteristics and are under similar processes as those of free-living species. This dissertation is mainly about infracommunity structure and its population interactions. It is divided in three chapters, all using bats and their ectoparasites as model of study. In the first chapter, I used the metacommunity framework, more specifically the metacommunity pattern-based approach, to identify infracommunity patterns of ectoparasites on three bat species in the Pantanal. These species are Artibeus planirostris (Phyllostomidae), Myotis nigricans (Vespertilionidae) and Noctilio albiventris (Noctilionidae). Contrasting to most studies that use only one taxonomic group of ectoparasites, I identified the structure of infracommunity of all taxa assembled, as well as for each class (Insecta and Acarina) separately. For all three bat species, the infracommunity structure for all taxa assembled were the same, Clamped species loss, which one presented the ‘quasi’ version. The insect and acari infracommunities structure pattern were different of the pattern found for the total species for N. albiventris and M. nigricans, Artibeus planirostris’s Acari structure pattern was the only one equal to total’s structure. These results showed that the exclusion of taxa while performing the Elements of Metacommunity Structure (EMS) analyzes can lead to misinterpretations and so I recommend that always use all species present. The second chapter is about the effect of forest cover, the host characteristics, and the interaction between ectoparasites in the structure, abundance, and agglomeration of these ectoparasites in the infracommunities. For this I used a 2-year dataset from the Serra da Bodoquena. I found that the nested Random species loss structure was the most frequent for bat ectoparasites in this region. The number of quasi structures was less frequent in areas with higher forest cover, indicating a stronger effect of structuring processes. Also, the agglomeration (ICr) was higher on bats from areas with lower forest cover, maybe because of less availability of suitable roosts. Regarding the interaction between ectoparasite species, I found no evidence of competition but found an increase in the mean intensity of infestation of two species as the number of species increases in the infracommunity. So, there may be a facilitation process, or these species benefit from the same host conditions that led them to accumulate greater richness and abundance of ectoparasites. Finally, in the third chapter I tested the ectoparasites density-dependent sex ratio hypothesis, in which female ectoparasites would be more aggregated in some host individuals from the same host species, presumably due nutritional demands, whereas males would be more dispersed across host individuals. For this I used a large sample of Anoura geoffroyi captured in two caves of Minas Gerais with dip nets during daytime. I found results that did not corroborate with the density-dependent hypothesis but found that female hosts were more infested by Exastinion clovisi than males. I suppose that this happens due to lack of mobility as this was the only species found without the ability to fly, although there’s no study evaluating the mobility capacity of these flies.